2014
DOI: 10.1108/hff-02-2013-0070
|View full text |Cite
|
Sign up to set email alerts
|

A conjugate axisymmetric model of a high-pressure shock-tube facility

Abstract: Purpose -An axisymmetric shock-tube model of the high-pressure shock-tube facility at the Texas A&M University has been developed. The shock tube is non-conventional with a non-uniform cross-section and features a driver section with a smaller diameter than the driven section. The paper aims to discuss these issues. Design/methodology/approach -Computations were carried out based on the finite volume approach and the AUSM þ flux-differencing scheme. The adaptive mesh refinement algorithm was applied to the tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The work of Lamnaouer et al 31 provided insight into the nature of the nonuniform conditions, showing temperature and pressure gradients behind reflected shock waves when bifurcations were present. As observed from the color schlieren images of Kleine et al, 28 all features of the bifurcation were seen in simulations done by Lamnaouer et al 31 These include features such as the bifurcated foot of the reflected shock wave; the separation bubble from the boundary layer under the oblique shocks; and, critical to the understanding of hotspots, swirling fluid of the shear layer and wall jet. Lamnaouer et al also showed the presence of local hotspots in the wall jet after the passage of the bifurcation.…”
Section: Experimental Nonidealitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The work of Lamnaouer et al 31 provided insight into the nature of the nonuniform conditions, showing temperature and pressure gradients behind reflected shock waves when bifurcations were present. As observed from the color schlieren images of Kleine et al, 28 all features of the bifurcation were seen in simulations done by Lamnaouer et al 31 These include features such as the bifurcated foot of the reflected shock wave; the separation bubble from the boundary layer under the oblique shocks; and, critical to the understanding of hotspots, swirling fluid of the shear layer and wall jet. Lamnaouer et al also showed the presence of local hotspots in the wall jet after the passage of the bifurcation.…”
Section: Experimental Nonidealitiesmentioning
confidence: 99%
“…Ever since bifurcation was first observed by Mark in 1958, much work has been conducted to investigate bifurcation from experimental and numerical perspectives. , Of some of the insights gained from these works, a couple to note are the change in bifurcation length with changing mixture composition and the presence of nonuniform conditions after passage of the bifurcated reflected shock wave. The work of Lamnaouer et al provided insight into the nature of the nonuniform conditions, showing temperature and pressure gradients behind reflected shock waves when bifurcations were present.…”
Section: Experimental Nonidealitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Quasi-one-dimensional and axial numerical simulations of reflected shock and boundary layer interactions reproduced the shock bifurcation by Wilson et al (1995). Lamnaouer et al (2014) developed an axisymmetric shock-tube model with a non-uniform cross-section, which can capture the detailed bifurcation structure with very good resolution, and they discovered a possible existence of hot spots in the end-wall region triggering early non-homogeneous ignition events. The numerical results by Gamezo et al (2001Gamezo et al ( , 2005 showed that the bifurcation creates a recirculation region attached by the shock that could act as a flame holder, which leads to an increase in energy release rate, and is in favor of triggering deflagration-to-detonation (DDT).…”
Section: Introductionmentioning
confidence: 92%
“…To elaborate on consequential nonuniformities that are presented in bifurcating systems, previous numerical work of Lamnaouer et al [38] revealed temperature and pressure gradients behind reflected shock waves, as well as hotspots in the wall jet after the passage of the bifurcation. In addition, Yamashita et al [35] provide support for localized hotspots in bifurcated flows, and with recent work of Lipkowicz et al [36] it was shown that various gas dynamic and fluid dynamic structures occurred at a distance from the end wall supporting these localized nonuniformities due to the bifurcated shock.…”
Section: Nonidealities Of the Systemmentioning
confidence: 99%